Analyzing the music of living composers (and others) - Boss, Jack Forrest; Osborn, Brad; Pack, Timothy Shane, 1969-; Rodgers, Stephen, 1974- (Cambridge Scholars, 2013)
Analyzing the Music of Living Composers (and Others) is a collection of essays that grew out of the 2010 annual meeting of the West Coast Conference of Music Theory and Analysis. The stated purpose was to apply traditional music-analytic techniques, as well as new, innovative techniques, to describing the music of composers of the late 20th and early 21st centuries. The goal was to take steps toward making the music of our time a bit less impenetrable for our colleagues, students and other li ...